2021
DOI: 10.34172/ijhpm.2021.163
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Health Sector Fiscal Decentralisation on Availability, Accessibility, and Utilisation of Healthcare Services: A Panel Data Analysis

Abstract: Background: Fiscal Decentralisation (FD) is a widely implemented decentralisation policy consisting of the allocation of pooling and spending responsibilities from the central government to lower levels of governance within a country. In 2001, The Italian National Health System (SSN) has introduced a strong element of FD, making regions responsible for their own pooling of resources and for their budgets. Despite the relevance, only few studies exist on health sector-FD in Italy, mostly looking at the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 52 publications
1
31
0
1
Order By: Relevance
“…2 Such pattern of resource reallocation may have occurred, at least in part in Italy, given that Rotulo and colleagues also found that 'regional surpluses play a negative effect on hospital beds density… suggesting that regions with more fiscal space do not necessarily invest more in hospital resources. ' 3 As an example of how decentralised governance affected efficiency, consider Rotulo and colleagues' finding that fiscal decentralisation decreased 'the share of residents to total patients' within regions, therefore 'suggesting an increase in the share of patients moving from one region to another to seek treatment. ' 3 They cited a previous study in Italy 7 that shows such mobility, 'especially from regions with historically weaker healthcare services' 3 -a pattern that is in keeping with the 'voting with feet' mechanism.…”
Section: 'Voting With Feet' (Reflecting How Decentralization Exacerba...mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Such pattern of resource reallocation may have occurred, at least in part in Italy, given that Rotulo and colleagues also found that 'regional surpluses play a negative effect on hospital beds density… suggesting that regions with more fiscal space do not necessarily invest more in hospital resources. ' 3 As an example of how decentralised governance affected efficiency, consider Rotulo and colleagues' finding that fiscal decentralisation decreased 'the share of residents to total patients' within regions, therefore 'suggesting an increase in the share of patients moving from one region to another to seek treatment. ' 3 They cited a previous study in Italy 7 that shows such mobility, 'especially from regions with historically weaker healthcare services' 3 -a pattern that is in keeping with the 'voting with feet' mechanism.…”
Section: 'Voting With Feet' (Reflecting How Decentralization Exacerba...mentioning
confidence: 99%
“…3 As an example of how decentralised governance affected efficiency, consider Rotulo and colleagues' finding that fiscal decentralisation decreased 'the share of residents to total patients' within regions, therefore 'suggesting an increase in the share of patients moving from one region to another to seek treatment. ' 3 They cited a previous study in Italy 7 that shows such mobility, 'especially from regions with historically weaker healthcare services' 3 -a pattern that is in keeping with the 'voting with feet' mechanism. But what also needs to be acknowledged are previous analyses in Italy 7 and elsewhere 8 suggesting that poor sub-national units with wealthy neighbouring units can reap efficiency gains by strategically under-investing in selected health services in anticipation of their residents' use of cross-border services, or by formally outsourcing selected services to such neighbouring units.…”
Section: 'Voting With Feet' (Reflecting How Decentralization Exacerba...mentioning
confidence: 99%
“… 4 Recent theories on fiscal decentralization argue that subnational governments who finance a larger proportion of their spending with their own sources of revenue are more accountable towards their citizens improving the performance of their jurisdictions. 6 However, even though a considerable number of studies find a positive association between decentralization and health related outcomes, there are also a few exceptions in the literature, including the findings by Rotulo et al 7 On the other hand, a wide consensus exist among researchers on the impact of decentralization on promoting natural experiments and innovation, resulting in new services or initiatives in an effort of regions to politically compete against each other and attract voters. The experience from Germany over the COVID-19 pandemic offers one of the best examples of how flexibility and diversity in local policy making could be highly beneficial in promoting learning by doing.…”
Section: Rationale For Decentralization Of Health Servicesmentioning
confidence: 99%
“…On the other hand, decentralization is not without its costs and could bring about challenges of its own as pointed out by Rotulo et al 7 in the light of theItalian experience. In particular, one of the most common arguments made against decentralization as illustrated in the Italian case is the perpetuation or even exacerbation of regional disparities due to the weaker financial capacity of some regions, especially if decentralisation of financing is involved.…”
Section: Complexities and Challenges Of Health System Decentralizationmentioning
confidence: 99%
“…The Italian healthcare system is heavily decentralised [ 13 ]. Accordingly, the country’s pandemic response has been fragmented and inappropriate to the needs of the vulnerable population [ 14 ].…”
Section: Introductionmentioning
confidence: 99%